DEEP TIKTOK APPLIED METHOD IN UNDERSTANDING ENGLISH LEARNING (APPLIED IN GENERAL CLASS FOR VOCABULARIES) - Fariani S, Nelia; Wibowo, Sandi Nasrudin; Alkanan, Omer Mohamed Taha; Putri, Amelia Herdia (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2024)
Abstract—TikTok is an audio-visual social media. Currently the use of the TikTok platform among learners can make the users feel happy, apart from the fact that the videos made on this platform are set to musical effects from various genres, they can also provide more clear information, concise and informative, especially in learning English easily and quickly. To find out that learning using TikTok have a positive influence and about how far TikTok has an influence in increasing the interest on English learning is the purpose of this research. This research uses quantitative research by collecting questionnaire data using the Likert scale method and analyzed in descriptive way. The researchers used descriptive statistics as data analysis technique. The subject of this research are 63 learners at general class for vocabulary in Universitas Swadaya Gunung Jati. The results of this research show that there is a very significant effect of effectiveness between TikTok social media on English listening comprehension. The result of this research are TikTok application turned out to be effective in increasing the understanding of learners in English subjects by listening and make learners more interested in learning English.